Analisis Konsentrasi CO2 di Kawasan Pasar Wisata Bojonegoro - Evi Cici Kumala; Heri Mulyanti; Solikhati Indah Purwaningrum (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Carbondioxide (CO?) is one of the greenhouse gases that contribute to climate change and global warming. Indoor and urban CO? concentrations can affect air quality and human health. Pasar Wisata Bojonegoro is a central economic hub with high mobility and trading activities, which may increase CO? emissions. This study aims to identify peak CO? concentration hours in the area and compare them with the air quality standards set by the WHO. A quantitative research method was used, involving direct observation and measurement over 7 (seven) days at a single observation point. The results show that on weekdays, the peak CO? concentration occurred between 16:00 and 16:59 WIB, reaching 424 ppm, while the lowest concentration was recorded between 18:00 and 18:59 WIB at 351 ppm. On weekends, the peak concentration was 441 ppm between 16:00 and 16:59 WIB, while the lowest was 113 ppm between 21:00 and 21:59 WIB. Several weekdays recorded CO? concentrations exceeding the WHO standard (310–330 ppm), with the highest reaching 466 ppm. However, CO? concentrations on Thursdays and weekends remained within the acceptable limits. The conclusion of this study shows that the results of CO? concentration on weekdays (Monday, Tuesday, Wednesday, Friday) exceed the quality standard with CO? concentrations of 466 ppm, 462 ppm, 413 ppm, and 433 ppm. Meanwhile, on weekdays (Thursdays) and weekends, it meets the quality standards with CO? concentrations of 217 ppm, 243 ppm, and 267 ppm.